“Did I Say Cherry?” Error Patterns on a Blocked Cyclic Naming Task for Bilingual Children With and Without Developmental Language Disorder - McMillen, Stephanie (J Speech Lang Hear Res, 2020)
PURPOSE: Using a blocked cyclic picture-naming task, we compared accuracy and error patterns across languages for Spanish–English bilingual children with and without developmental language disorder (DLD). METHOD: Pictured stimuli were manipulated for semantic similarity across two (Same and Mixed) category contexts. Children's productions were scored off-line for accuracy, error frequency, and error type. RESULTS: Typically developing children were more accurate and produced fewer errors than their peers with DLD; however, this was moderated by task language and semantic context. Children were generally more accurate when naming pictures in English compared to Spanish and in the Mixed-category context compared to the Same-category context. Analyses of error types further showed that children with less English language exposure specifically produced more nonresponses in English than in Spanish. Children with DLD produced more of each error type than their typically developing peers, particularly in Spanish. CONCLUSIONS: Regardless of language ability, bilingual children demonstrated greater difficulty with lexical retrieval for pictured items in the semantically related context than in the unrelated context. However, bilingual children with DLD produced more errors of all types than is typical for children developing more than one language. Their greater error rates are not secondary to limited second language exposure but instead reflect deficits inherent to the nature of language impairment. Results from this study are discussed using a framework of semantic constraint, where we propose that because bilingual children with DLD have impoverished semantic networks, and this knowledge insufficiently constrains activation for lexical selection, thereby increasing error production.